Distributional and behavioural effects of the German labour market reform - Markus Clauss; Reinhold Schnabel (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
We estimate the effects of the reform of German Unemployment Insurance that replaced the wage-related Unemployment Assistance with an income maintenance Programme and stronger means testing. We model the tax-benefit system and use the Socio-Economic Panel. We estimate a discrete labour supply model and simulate the behavioural and distributional effects using the pseudo distribution method. Poverty and inequality decline overall, since households with children and low incomes gain, while those who used to earn high wages and received high unemployment transfers lose most. The behavioural responses mitigate the redistributive impact of the reform.
Keywords: 330; Arbeitsmarktpolitik; Verteilungseffekte; Einkommensverteilung; soziales System; Einkommenseffekte; Sozialleistungen; Arbeitslosengeld II-Empfänger; Arbeitslosengeld II; Einkommenshöhe; Familieneinkommen; soziale Gerechtigkeit; Erwerbsbeteiligung; Beschäftigungseffekte; Umverteilung; Armutsbekämpfung; Arbeitslose; Arbeitsuchende; Arbeitsuche; Erwerbsverhalten